Lixiviacion del nitrogeno en algunos suelos de la zona cafetera y su relacion con la textura - Arias S, E.=700 1 Sadeghian K, S.; Mejia M, B.; Morales L, C.S.
(Es, En)
Ilus., 39 ref.
Keywords: LIXIVIACION; UREA; NITRATO; AMONIO; ACIDEZ; PH DEL SUELO; EQUILIBRIO ACIDO-BASE; TEXTURA DEL SUELO; COLOMBIA